Through the eyes of students: the satisfaction of remote Indigenous boarding students’ with a transition support service in Queensland, Australia - Redman-MacLaren, Michelle; Benveniste, Tessa; McCalman, Janya; Rutherford, Katrina; Britton, Amelia; Langham, Erika; Stewart, Richard; Saunders, Pat; Kinchin, Irina; Bainbridge, Roxanne (The Australian Journal of Indigenous Education, 2019)
Abstract More than 4000 Indigenous Australian students enrol and take up a placement at boarding school each year. While reasons for attending boarding school vary, the impetus for many remote and very remote-dwelling students is restricted secondary educational opportunities in their home communities. A large multi-site study is being undertaken across Queensland to understand the conditions required for these students to be resilient while studying away from home. This paper reports on levels of student satisfaction with Queensland Department of Education's Transition Support Service (TSS) that provide assistance to remote-dwelling Indigenous students in the transition to boarding schools. A survey instrument administered to students included 22 close-ended questions to elicit levels of student satisfaction with TSS. Data were collected electronically using SurveyMonkey™ and analysed in SPSS v24. Descriptive statistics were calculated for variables assessing service support, student perceptions and experiences. A total of 294 primary, secondary and re-engaging students across 21 sites responded. Nearly all primary students (97%) anticipated that TSS would assist their move to boarding school. All secondary students identified that TSS had assisted their transition to boarding school. All re-engaging students agreed that TSS support had increased their capacity to cope when things go wrong. Lower scores related to students’ ability to access TSS when needed. Very high levels of satisfaction with TSS were countered by constraints of distance between TSS and students, and resources available to support the work of TSS. Findings point to the need for equitable provision of transition services in Queensland that emphasise the importance of relationship between service provider and student, and can inform the design of similar transition services across Australia.